Electrodiagnostic subtyping in Guillain‐Barré syndrome: Use of criteria in practice based on a survey study in IGOS. Issue 3 (24th June 2022) - Arends, Samuel; Drenthen, Judith; Van den Bergh, Peter Y.K; Hadden, Robert D.M.; Shahrizaila, Nortina; Dimachkie, Mazen M.; Gutiérrez Gutiérrez, Gerardo; Katzberg, Hans; Kiers, Lynette; Lehmann, Helmar C.; Péréon, Yann; Reisin, Ricardo C.; et al.
Abstract: Electrodiagnostic (EDx) studies are helpful in diagnosing and subtyping of Guillain‐Barré syndrome (GBS). Published criteria for differentiation into GBS subtypes focus on cutoff values, but other items receive less attention, although they may influence EDx subtyping: (a) extensiveness of EDx testing, (b) nerve‐specific considerations, (c) distal compound muscle action potential (CMAP)‐amplitude requirements, (d) criteria for conduction block and temporal dispersion. The aims of this study were to investigate how these aspects were approached by neuromuscular EDx experts in practice and how this was done in previously published EDx criteria for GBS. A completed questionnaire was returned by 24 (of 49) members of the electrophysiology expertise group from the International GBS Outcome Study. Six published EDx criteria for GBS subtyping were compared regarding these aspects. The indicated minimal number of motor nerves to study varied among respondents and tended to be more extensive in equivocal than normal studies. Respondents varied considerably regarding usage of compression sites for subtyping (median/wrist, ulnar/elbow, peroneal/fibular head): 29% used all variables from all sites, 13% excluded all sites, and 58% used only some sites and/or variables. Thirty‐eight percent of respondents required a minimal distal CMAP amplitude to classify distal motor latency as demyelinating, and 58% did for motor conduction velocity. For proximal/distal CMAP‐amplitude ratio and F‐wave latency, a requisite minimal CMAP amplitude was more often required (79%). Also, the various published criteria sets showed differences on all items. Practical use of EDx criteria for subtyping GBS vary extensively across respondents, potentially lowering the reproducibility of GBS subtyping. Abstract :